Comparison of apricot cultivars for suitability for organic growing - Dremák, Péter (Acta Agraria Debreceniensis, 2010)
Nowadays, important task is using more widely the environmentally friendly production technologies. There are considerable differences among technologies using reduced spray programs (integrated and organic) in plant protection and plant nutrition. In this case integrated production has a better position as roles for organic production more strict and due to this fruits has an obvious temporal and permanent reduction in tree conditions. Fitotechnical elements and renewal and regeneration of cultivars are important factors for offseting or delaying of condition weakening. In this study, 5 apricot cultivars (not pruned for 8 years) were compared in their characteristics (assessment of inactive, semi-active and active plant parts). Our study showed that there were 50-70% differences among observed characteristics. Our study confirmed those cultivars which are suitable for organic production and which one more resistant to condition weakening and which one able to tolerate negative technological effects.